Influence of Spatial and Temporal Distance of the Hospital on Survival of Patients with Dangerous Injuries Sustained in Traffic Accidents - Damir Pelicic; Branko Ristic; Nemanja Radojevic; Nela Djonovic; Svetlana Radevic (Tehran University of Medical Sciences, 2022)
Background: Effective care of any trauma is a priority in all health care systems. If a patient gets adequate treatment within "golden hour" from the injury the prognosis is better, but not as the only factor. The objective was focused on the influence of time and spacial distance of the hospital from the accident as determinant factors of survival, all in the aim Public Health System of Montenegro reorganisation for better accessibility for traumatized persons from 2011-2020. Methods: Among 334 subjects, three groups were defined according to the type of injury: bleeding, ashpyxiations, and cranio-cerebral injuries. In every group lethal and non-lethal subjects were analyzed. Results: Cut-off values are given by ROC curves following proximity and transportation time to hospital specific for injury sustained, as well as for nearest hospital, showed significant differences for proximity of any hospital for bleeding and asphyxiation injuries, and for proximity of any hospital and transportation time to the hospital specific for the sustained cranio-cerebral injury. Conclusion: Most of the seriously injured patients with bleeding or asphyxiation could be taken care of in any hospital while for cranio-cerebral injuries the specific hospital is crucial. How it is very often about, different organ systems are usualy injured in single patient, so the forming of easily available trauma centers net is the best solution for Montenegro, which is necessary for better survival rates.